Use of Earth Observation data and Google Earth Engine monitoring and early warning of floods and droughts - Amarnath, Giriraj (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
A total of 24 participants were represented from 8 institutions (WARMA, ZMD, Ndola City Council, IAPRI, Mulungushi University, ZRCS, NRSC and ZAMSTATS). Technical experts introduced with a presentation on the potential application of flood and drought monitoring and early warning using geospatial data, tools and models including earth engine (EE). The various example presented to participants to get an understanding of the EE capabilities and how the training provides an opportunity to utilize the remote sensing products in a timely decision making process. Later the experts delivered a lecture on the basics of remote sensing and GIS to help understand the characteristics of remote sensing sensors and their capabilities in mapping and monitoring environmental issues.